Impact of climate change on water resources, rice production and income in Ca Mau Province, Vietnam - Duong Anh Tran; Clemente, Roberto S.; Jourdain, Damien; Shresth, angam; Perret, Sylvain Roger; Swedish International Development Agency (SIDA) (Pathum Thani : Asian Institute of Technology, 2012)
Impact of climate change on water resources and agriculture secto r has become a tremendous problem for many countries as increase in water demand, population growth, and food security are observed. Vietnam is one of most affected country by climate change in the world, with many areas prone to storm, cyclone, heavy rain fall and other extreme events . Reducing of rice production and income will affect to socio - economic development and first, seventh millennium development goals in developing countries in general, in Vietnam particular. Consequently, studying the impact of climate change on water resources, agriculture and income that investigate how climate condition in the future affect to rice yield, agricultural income variation, has been the focus of this study. RClimdex has been use to analyze of historical climate da ta. The analysis revealed that average annual temperature annual precipitation increased in the past. Future climate of Ca Mau is generated by statistical downscaling model (SDSM 4.2) from output of HadCM3 General Circulation Model for A2, B2 scenarios def ined by IPCC. It is found that maximum temperature would be increased up to 4.03 o C and 4.01 o C and annual precipitation would be increased up to +31.1% and 24.1% under A2 and B2 scenario, respectively. The research also apply AquaCrop model to simulate th e growing cycle and yield of rice crop . The predicted rice yield shows a significant ly increase in summer - autumn cycle and unsubstantial decrease i n autumn - winter cycle under scenario 1 (full application of fertilizer and irrigation ) . The rice yield simula ted for scenario 2 (full application of fertilizer and at 75% FC) shows the substantial rice yield reducing in both summer - autumn and autumn - winter cycle and rise up for autumn - winter cycle. The study also indicates that, the irrigation water of this area is not fairly suitable for irrigation purpose as it falls under category {u2018}slight to moderate{u2019} by effect of saline concentration. Net income of rice cultivation may be increased by 14.3% and decreased by 31% to 57% compared to income of rice production in 2 011 under 3 scenarios in the year of 2020 because of temperature variation and precipitation changes
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering Management
Thesis (M.Eng.) - Asian Institute of Technology, 2012
Keywords: Water-supply, Agricultural -- Vietnam -- Ca Mau; Climatic changes -- Vietnam -- Ca Mau